Satisfacción de los clientes residenciales de Movistar del servicio de tv cable en la ciudad de Trujillo, mayo 2014 - Ponce Chancán, Miguel Angel (2014)
The present study aimed to determine the level of satisfaction among residential customers of Movistar cable tv service in the city of Trujillo, in May 2014, the investigation was based on a descriptive cross-sectional study was used as the survey instrument to measure Customer satisfaction cable tv service, which consists of three dimensions (operation, programming, use and operation of the decoder) with Likert scale, a simple random sample of 196 customers of Movistar TV. Statistical analysis was divided into two parts, the first refers to the evaluation of the dimensions of the modeled satisfaction survey, and it was determined that the level of satisfaction among residential customers is average 52%. The second statistical analysis referred to a multivariate analysis of that by the dendrogram was obtained that customers were classified into 3 classes as: Class 1 named class of satisfied customers in the dimensions of programming and usage-operation of the decoder, which consists by 70.41% of customers. Class 2 called class completely satisfied customers in the dimensions of-use programming and operation of the decoder, which consists of the 22.96% of customers. And finally the class named Class 3 moderately satisfied customers in the dimension of programming, which is made up 6.63% of the customers